A longitudinal examination of leisure time physical activity following amputation in England. (July 2018) - Wadey, Ross; Day, Melissa
Abstract: Objectives: There is a significant body of research on leisure time physical activity (LTPA) among people with physical disabilities. Yet, while this data set has been informative in identifying the social-relational factors that affect LTPA across disability groups, there is now a demand for context- and population-specific studies to provide a more nuanced understanding to better inform decision-makers and service-providers. This original study is the first to examine the barriers, facilitators, and benefits of LTPA among people with an amputation in England. Methods: Multi-method, longitudinal research design (from April 2014 to May 2016). Participants were recruited using maximum-variation and criterion-based purposeful sampling. Data collection included two focus groups (>4hrs), fieldwork observations (>225hrs), and 44 formal interviews (>50hrs). Practical strategies used to support or evidence the study's quality in terms of its credibility, rigour, generalizability, and significance included author self-reflexivity, member reflections from participants, and external reflections with key stakeholders before seeking publication. This large qualitative dataset was rigorously analysed using inductive thematic analysis. Results: Ten themes were identified: personal wellbeing, social wellbeing, physical wellbeing, inspiration, self-presentation, experience of LTPA, knowledge of LTPA, environment, organisational functioning, and miscellaneous. Conclusions: This article makes a novel and significant contribution to research by revealing the dynamic and relational nature of barriers, facilitators, and benefits. Practical implications for LTPA policies and practices are considered through a social ecological lens (i.e., intrapersonal, interpersonal, institutional, community, and policy). Highlights: An original and rigorous examination of leisure time physical activity (LTPA) among people with an amputation in England. Factors implacting LTPA in England are dynamic, fluid, and relational. Findings provide a rigorous foundation for a 'bottom up' approach for LTPA promotion (NHS England, 2014). Practical implications are considered at an intrapersonal, interpersonal, insitutional, community, and policy level.